Chance Events and Career Decidedness: Latent Profiles in Relation to Work Motivation. Issue 1 (March 2017) - Hirschi, Andreas; Valero, Domingo
Abstract : Research has shown that chance events affect careers but has not established the nature of their effects. Moreover, the relationship between chance and career decidedness is not well understood. The authors used a person‐centered approach with latent profile analysis to examine 312 Swiss adolescents in their 1st year of vocational training. The authors identified 5 qualitatively differing profiles according to levels of perceived chance events and career decidedness: balanced scorers, undecided with mean chance, undecided with high chance, decided with chance, and decided without chance. The groups differed significantly in work motivation (i.e., occupational self‐efficacy beliefs, perceived person–job fit, and work engagement). Decided adolescents reported more favorable work motivation regardless of their level of perceived chance events. The results imply that promoting decidedness remains a valuable goal in career counseling despite the occurrence of unpredicted events.